Core para sincronismo de símbolo na recepção de sinais de satélite no padrão DVB-RCS - Prates, Wagner Santos Siqueira (2016)
Digital communication links, whether wireless, optical or cable, transport information from the origin point to the destination point by means of an Electromagnetic (EM) wave. The wave propagates in the physical medium between two points in the link with a velocity which depends on the electrical permittivity and on the magnetic permeability of the medium. In general, the propagation velocity is close to the speed of light in vacuum. The digital information transported by the link is the consequence of the digital system to vary the amplitude, the phase, or the frequency of the EM wave in accordance with the binary words to be transported. This process of variation of the EM wave definition parameters in accordance with the binary words to be transported is called digital modulation. The propagated EM wave has its defining parameters sequentially varied depending on each respective binary word sequentially transmitted through the link. Each binary word occurs within a certain fixed length time window, and, as a result, the EM wave maintains constant the value of its defining parameters during said time window. Since the wave propagates in the medium with constant speed, just as in the time window, the wave keeps the value of its defining parameters for a spatial window along its propagation path. Thus, the EM wave is modularized along its propagation path in modules that occur corresponding to the spatial windows. In this context, each module or window along the EM wave is parameterized by the corresponding binary word, and each such parameterized module is thus interpreted by the system as a digital modulation symbol which symbolically represents the information expressed in the respective binary word associated with the window. Therefore, it is crucial for the intelligibility of the signals that reach the receiver at the destination point that the link operates under the condition of perfect synchronization between the time window for the symbols emitted by the transmitter with the time window for the symbols to be received by the link receiver. Not being aligned temporally with the transmitter symbol time window, the symbols captured by receiver symbol time window would contain information from both two adjacent symbols, which establish the condition of inter-symbol interference, causing uncertainty and compromising the signal intelligibility for all subsequent blocks of the system. In this context, this work aims to develop and implement an IP Core for symbol synchronization for satellite signal receivers in the DVB-RCS standard (Digital Video Broadcasting - Return Channel System). The research will be directed towards getting an innovative solution with respect to aspects of performance and computational cost of the system, and to be able to meet the demands, whether in broadband communications or in defense area.